How do Mandibular Osteotomies with and without Le Fort I osteotomy affect the Mentolabial Groove from the frontal view? - Sina Uçkan; Muazzez Suzen; Abdullah Özel; Emrah Dilaver (Selcuk Dental Journal)
Purpose: The aim of this study was to determine how the mentolabial groove at the frontal view is affected by orthognathic surgery. Materials & Methods: Sixty-two patients were appointed into two groups (Group 1: Class II skeletal deformity, Group 2: Class III skeletal deformity). In each patient, pre and postoperative standardized sixth-month photos (lateral and frontal view) were obtained in natural head position to investigate mentolabial groove length (MGL), mentolabial groove depth (MGD), mentolabial groove angle (MGA) and mentolabial angle (MLA). Results: Out of the 62 patients, 41 had Class III skeletal deformity (66.2%) and 21 Class II skeletal deformity (33.8%). In Group 1, the average ratio of MGL decreased significantly from 0.59±0.14 to 0.45±0.09 (p<0.001). Contrary to Group 1, the ratio of MGL increased significantly from 0.41±0.11 to 0.50±0.13 in Group 2 (p=0.001). There was a negative correlation between MGA and MGL (p=0.001, r=-0.439). MGD positively correlated with MGL (p<0.001, r=0.499). Conclusion: After orthognathic surgery, the mentolabial groove decreases in class II patients and increases in class III patients. Orthognathic surgery significantly affects mentolabial anatomy and therefore should be planned carefully to obtain an aesthetic appearance in the mentolabial region.